2021
DOI: 10.1016/j.ijppaw.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

New geographic records for Echinococcus canadensis in coyotes and moose from Nova Scotia, Canada

Abstract: Echinococcus spp. tapeworms can cause serious diseases in mammals, including humans. Within the E. granulosus species complex, metacestodes produce unilocular cysts that are responsible for cystic echinococcosis in animal intermediate hosts. Canids are definitive hosts, harbouring adult cestodes in their intestines. Adult E. canadensis were recovered from the small intestine of 1 of 262 coyotes ( Canis latrans ) from Nova Scotia, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A domestic cycle of transmission involving domestic dogs and farmed elk was also identified in western Canada (Thompson, 2013). Recent reports of E. canadensis in coyotes in Canada suggest the emergence of this species in new endemic regions (Santa et al , 2018; Priest et al , 2021) and given that, the urbanization of the coyote in Canada is of potential public health significance.…”
Section: Wildlifementioning
confidence: 99%
“…A domestic cycle of transmission involving domestic dogs and farmed elk was also identified in western Canada (Thompson, 2013). Recent reports of E. canadensis in coyotes in Canada suggest the emergence of this species in new endemic regions (Santa et al , 2018; Priest et al , 2021) and given that, the urbanization of the coyote in Canada is of potential public health significance.…”
Section: Wildlifementioning
confidence: 99%
“…Dog owners in Newfoundland should be aware of this risk and avoid feeding uncooked meat or organs from hunted cervids to their dogs, as well as consult their veterinarian regarding regular deworming of dogs to protect human health. Hydatid cysts in the lungs or livers of moose and caribou pose no food safety risk to people, but if consumed by dogs or wild canids they can develop into adult tapeworms and pass eggs in feces that are immediately infective to people (Priest et al 2021).…”
mentioning
confidence: 99%
“…Within Canada, insular Newfoundland, Nova Scotia, New Brunswick, and Prince Edward Island have previously been considered free of E. canadensis due to the absence of wolves ( Canis lupus ) as definitive hosts (Schurer et al 2013), but over the last decade there have been reports and genetic evidence of Labrador wolves ( Canis lupus labradorius ) in insular Newfoundland (Callahan, unpublished data). Recently E. canadensis was documented in moose from Nova Scotia (Priest et al 2021) and a hydatid cyst, the form seen in intermediate hosts, was found in the lung of a moose harvested in 2018 from Gros Morne National Park, insular Newfoundland (Pollock, provincial veterinarian, pers. comm.).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…parasite tissue are laborious tasks (Moks et al, 2008;Schurer et al, 2013;Romig et al, 2017). However, by analyzing selected mt loci, predominantly cox1 and/or nad1 gene fragments, available studies have provided valuable first insight into the genetic variation of these genotypes (e.g., Lavikainen et al, 2006;Moks et al, 2008;Nakao et al, 2013;Schurer et al, 2013;Yang et al, 2015;Dell et al, 2020;Priest et al, 2021). For example, such studies have indicated that the extent of genetic variation within the two E. canadensis genotypes (G8 and G10) is considerably lower and less complex than within other Echinococcus species or genotypes, such as E. granulosus sensu stricto (s.s., G1/G3) and G6/G7 of the E. canadensis cluster (Romig et al, 2015;Kinkar et al, 2018a, b;Laurimäe et al, 2018b).…”
mentioning
confidence: 99%